Evaluation of an After-School Obesity Prevention Program for Children - Nabors, Laura; Welker, Kristen; Pavilack, Brandon; Lang, Myia; Hawkins, Renee; Bauer, Anne (International Journal of Child Health and Nutrition, 2018)
Dissemination of obesity prevention programs in different settings is needed. Moreover, new outreach tools to teach parents healthy eating and exercise lessons provided in these programs are important to develop. The pilot studies presented in this paper examined the implementation of the Children’s Healthy Eating and Exercise Program in two different after school programs in 2015 and 2016. Participants were elementary school-age children and their parents. Eight lessons were presented at each school. Child perceptions of healthy eating and exercise goals were examined as well as child knowledge retention and perceptions of behavior change. Parent perceptions of the program were analyzed. Results indicated that children reported improved knowledge and behaviors. Parents reported satisfaction with the program, but remained hard to reach. Children recalled key components of the healthy eating lessons at long-term follow-up assessments. In the second pilot study, children served as health coaches for teaching parents about family goals. Children believed they were successful at coaching parents, but they requested help in developing family eating and exercise goals. Improving outreach to parents and involving siblings remains a goal for future studies as does beginning to examine changes in eating and physical activity using food diaries and accelerometry.